Analysis of Age, Smoking Habit, Nutritional Status, and Their Influence on Hypertension - Wismoyo Nugraha Putra; Bayu Satria Wiratama; Rachmah Indawati; Diah Indriani (Jurnal Berkala Epidemiologi, 2021)
Background: Hypertension is a major risk factor for cardiovascular disease that can lead to death; it is a condition that is related to age, nutritional status and smoking habit. The likelihood of a person being overweight or obese increases every year, and there are still many people who have a smoking habit. Purpose: This study aims to analyze the effect of age, smoking habit and nutritional status on incidences of hypertension in East Java Province. Methods: This was an analytical observational study using a cross-sectional design and employing secondary data derived from the 5th Indonesian Family Life Survey (IFLS). Data collection was carried out among all household members in East Java who were still at a productive age (15–64 years) making a total of 3,803 respondents. The variables observed were age, gender, nutritional status, smoking habit, physical activity, and consumption of high-fat foods. The data analysis used the chi-squared test and logistic regression. Results: The findings of this study show that there is a relationship between age and nutritional status and the incidence of hypertension. However, there was no significant relationship between smoking habit and the incidence of hypertension. Elderly respondents were shown to have 12 times the risk of developing hypertension than teenage respondents. Conclusion: Age is the dominant factor causing hypertension in East Java Province. Adults and the elderly in East Java Province are expected to maintain a healthy lifestyle.